BRCA1 and p53 regulate critical prostate cancer pathways - de Luca, Paola (2013)
Background: Loss or mutations of the BRCA1 gene are associated with increased risk of breast and ovarian cancers and with prostate cancer (PCa) aggressiveness. Previously, we identified GADD153 as a target of BRCA1 protein, which increases doxorubicin sensitivity in human p53 −/− PCa cells (PC3). Considering that p53 is a crucial target in cancer therapy, in this work we investigated p53 role in the regulation of transcription of GADD153. Methods: We performed reverse transcription quantitative PCR (RT-qPCR), western blot and luciferase assays to analyze GADD153 and/or BRCA1 expression in response to ultraviolet or doxorubicin exposure in PC3 p53 stable-transfected cells and LNCaP (p53+/+) cells. BRCA1 protein recruitment to GADD153 promoter was studied by chromatin immunoprecipitation-qPCR. To assess expression of BRCA1 and/or p53 target genes, we used a panel of stable-transfected PCa cell lines. We finally analyzed these genes in vivo using BRCA1-depleted PCa xenograft models. Results: We found that GADD153 was highly induced by doxorubicin in PC3 cells; however, this response was totally abolished in LNCaP (p53wt) and in p53-restituted PC3 cells. Furthermore, BRCA1 protein associates to GADD153 promoter after DNA damage in the presence of p53. Additionally, we demonstrated that BRCA1 and/or p53 modulate genes involved in DNA damage and cell cycle regulation (cyclin D1, BLM, BRCA2, DDB2, p21WAF1/CIP1, H3F3B, GADD153, GADD45A, FEN1, CCNB2), EMT (E-cadherin, β-catenin, vimentin, fibronectin, slug, snail) and Hedgehog pathways (SHH, IHH, DHH, Gli1, PATCH1). Furthermore, xenograft studies demonstrated that BRCA1 knockdown in PC3 cells increased tumor growth and modulated these genes in vivo. Conclusions: Although BRCA1 induces GADD153 in a p53 independent manner, p53 abolished GADD153 induction in response to DNA damage. In addition, several important PCa targets are modulated by BRCA1 and p53. Altogether, these data might be important to understand the therapy response of PCa patients.